2018
DOI: 10.1111/aos.13807
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peripapillary choroidal thickness in patients with multiple sclerosis

Abstract: Purpose: To study peripapillary choroidal thickness (PPCT) around the optic disc and establish zones using a new swept source optical coherence tomography (SS-OCT) device. To evaluate PPCT differences between patients with multiple sclerosis (MS) and age-and sex-matched healthy controls. Methods: A total of 102 healthy subjects and 51 patients with MS were consecutively recruited. Healthy subjects were divided into teaching (n = 51, used to establish choroidal zones) and validating (n = 51, used to compare mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…A reduction of ganglion cell number contributes to the reduction of retinal volume correlating with the superficial and deep capillary layers. Our results regarding choroidal thickness confirmed the results of Esen et al and Garcia-Martin et al [39,40], which suggest a potential role for vascular dysregulation in the pathophysiology of MS. We suggest that a reduction of GCC and, consequently, of the retinal tissue, implies a loss of vascularization at this level. We propose that the reduction of retinal tissue, including the loss of GCC and RNFL found by SD-OCT, leads to hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…A reduction of ganglion cell number contributes to the reduction of retinal volume correlating with the superficial and deep capillary layers. Our results regarding choroidal thickness confirmed the results of Esen et al and Garcia-Martin et al [39,40], which suggest a potential role for vascular dysregulation in the pathophysiology of MS. We suggest that a reduction of GCC and, consequently, of the retinal tissue, implies a loss of vascularization at this level. We propose that the reduction of retinal tissue, including the loss of GCC and RNFL found by SD-OCT, leads to hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…With this technique, the visual pathway is recognized as a model for correlating retinal neurodegeneration and disability in MS and some authors have demonstrated its potential as an early diagnostic tool [7]. In addition, the latest OCT software provides measurements of each retinal layer and even measurements of the choroidal plexus, which seems to provide more accurate measurements of axonal damage and ischemic processes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Satue et al ( 105 ) also showed that both macular and peripapillary CT were higher in patients with Parkinson's disease than in healthy controls. Garcia-Martin et al ( 106 ) reported that peripapillary CT was lower in patients with multiple sclerosis than in age- and sex-matched controls. Macias et al ( 107 ) studied the choroidal changes in astronauts with space-flight-associated neuro-ocular syndrome and found that peripapillary choroid thickening, along with disc edema, developed gradually during spaceflight and persisted for up to 30 days after the mission.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%
“…This close relationship highlights the optic nerve, and meaningful quantitative alterations in retinal thickness and volume have been demonstrated in patients with cognitive impairment and neurodegenerative diseases ( 19 , 112 ). In addition, a growing number of studies have analyzed peripapillary CT in neurologic diseases ( 101 106 ). Andrade et al ( 101 ) demonstrated that macular CT was significantly reduced in patients with Huntington's disease compared to that in controls.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%